Intermetallic phase precipitation and oxidation behavior of Fe–20Cr–0.5Nb–2Mo (at%) high-Cr ferritic alloy at high temperatures. (1st March 2023) - Kondo, Shintaro; Chai, Yaw Wang; Kanai, Kentaro; Dosung, Lee; Watanabe, Manabu; Ishikawa, Shin; Yamasita, Takako; Kimura, Yoshisato
Abstract: The precipitation behavior of intermetallic compounds, such as C14 Laves phase and Chi (χ) phase, and oxidation behavior of an Fe–20Cr–0.5Nb–2Mo (at%) high-Cr ferritic alloy were investigated at high temperatures between 1023 K and 1123 K. During aging/oxidation heat treatment at 1073 K, the protective Cr2 O3 is rapidly formed on the surface, consecutively, a high density of fine Laves precipitates, (Fe, Cr)2 (Mo, Nb), are formed throughout the α-Fe matrix and preferably at the α/Cr2 O3 interfaces as well as α-Fe grain boundaries. The Laves precipitation causes local changes of solute concentrations in the surrounding α-matrix, i.e., decrease in Nb and increase in Mo. These local changes of phase equilibria in the vicinity of the α-grain boundaries and α/Cr2 O3 interfaces result in the formation of the χ-phase which is not supposed to be precipitated. Moreover, χ precipitation at the α/Cr2 O3 interfaces is most favored in case the alloy is oxidized at 1073 K. In the short-term oxidation at 1073 K, the Cr-rich χ interfacial precipitates, Fe36 Cr12 (Mo8, Nb2 ), suppress the growth of Cr2 O3 . However, as the interfacial χ precipitates coarsen in the long-term oxidation at 1073 K, localized stress concentrations are generated at intersections between the Cr2 O3 layer and the α/χ interfaces. Consequently, these facilitate cracking of the adjacent surface oxide, then oxide 'rehealing', and formation of the abnormal-Cr2 O3 process. Eventually, the precipitation of interfacial χ phase indirectly causes an acceleration growth of the surface Cr2 O3 on the alloy. Graphical abstract: Image, graphical abstract